Amino acid T25 in the substrate-binding domain of SARS-CoV-2 nsp5 is involved in viral replication in the mouse lung. - Yoshiro Sugiura; Kenta Shimizu; Tatsuki Takahashi; Shiori Ueno; Haruka Tanigou; Sodbayasgalan Amarbayasgalan; Wataru Kamitani (PLoS ONE)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) non-structural protein 5 (nsp5) is a cysteine protease involved in viral replication and suppression of the host immune system. The substrate-binding domain of nsp5 is important for its protease activity. However, the relationship between nsp5 protease activity and viral replication remains unclear. We confirmed the importance of amino acid T25 in the nsp5 substrate-binding domain for viral replication using a split luciferase assay. By generating recombinant viruses using bacterial artificial chromosomes, we found that the proliferation of viruses with the T25I mutation in nsp5 was cell-dependent in culture. Furthermore, mice infected with the T25I mutant recombinant virus with a mouse acclimation backbone showed weight loss and increased lung viral load, similar to the wild-type (WT) infected group, up to 3 days after infection. However, after day 4, the lung viral load was significantly reduced in the T25I-infected group compared to that in the WT-infected group. This suggests that nsp5 T25 is involved in the pathogenesis of SARS-CoV-2.